(untitled) (PRÁXIS EM SAÚDE, 2025)
Objective: To report the application of CBT techniques adapted for an adolescent with a history of sexual violence, neglect, and exposure to violence, focusing on emotional regulation and rebuilding self-esteem. Method: Single case study (16 sessions) with a female patient, 18 years old. Psychoeducation, cognitive restructuring, coping skills training, and narrative exposure were used. The evaluation consisted of clinical follow-up. Results: Reduction of anxiety and stress, decrease in self-harming behaviors, and greater ability to question core beliefs. However, residual difficulties were observed in memory problems and adherence to leisure activities. Conclusion: CBT proved promising in managing the adolescent in trauma contexts but requires adaptations for patients with a history of prolonged invalidation.